A cross-sectional study on the factors influencing juvenile delinquency in the government juvenile home, Hyderabad, Telangana - Vemuri, Jyothi Lakshmi Naga; Rao, R. L. Lakshman; Roohen, Sara; Kiranmayee, G. (International Journal Of Community Medicine And Public Health, 2019)
Background: Juvenile is a boy who has not attained 16 yrs and a girl who has not attained 18 yrs. Any offence thefts/robbery, attempt to murder/murder, rape, addictions and any deviation from normal behavior like truancy, vandalism, immorality and ungovernability is termed as delinquency. According to National Crime Records Bureau (NCRB) (2016), Telangana is holding 16th rank and among the metropolitan cities, Hyderabad is contributing to 11th rank based on percentage share in India on Juvenile crime. The objective of the study was to study the factors influencing the juvenile delinquency. Methods: An institutional based cross-sectional study is carried out for a period of three months in the Government Juvenile homes of Hyderabad, Telangana. All the inmates of the male and female juvenile homes (n=200) available at the time of study who were willing to participate were interviewed. Those who were sick and not cooperative were excluded. A semi-structured questionnaire completed through interviews and studying the subjects’ records and ISRD3 questionnaire were used. Institutional ethical clearance was taken before starting the study. Results: 77.5% (155) were males and 22.5% (55) were females. 16.5% (33) were 6-10 yr age group and 83.5% (167) were above 11 yrs. The mean age (yrs) is 14.02±2.96. 18% (36) didn’t attend school and 82% (164) attended school. Age, sex, school attending and the time spent with the parents have shown significance (p<0.05) in the delinquency. Conclusions: The peer influence, smart phone usage, influence of movies and truancy from home also showed significance (p<0.05) in the delinquency.